ECOLOGICAL BAKING OF WHEAT BREAD USING HOP SOURDOUGHS AND SPIRULINA - Zhemela, Hr. P.; Bahan, A. V.; Barabolia, O. V.; Shakaliy, S. M.; Chaika, T. O. (Scientific Progress & Innovations, 2020)
At present, there is a growing demand in the society for organic products that are environmentally safe and natural. Therefore, along with applying accelerated production technologies, manufacturers are return- ing to the classical technologies, which ensure high quality products. One of such technology is the technol- ogy of baking bread on hop sourdoughs, which in its time was used mainly for baking bread from minor- quality and crude flour. The main argument in favor of bread baking technology on hop sourdough is that this bread can be baked without using pressed yeast. The purpose of the study was to investigate the rheolog- ical, bread baking and organoleptic characteristics of bread baked from Orzhytsia wheat cultivar on various hop sourdoughs with the addition of spirulina. For baking bread, Orzhytsia soft winter wheat cultivar, wild hop, and also wheat-hop sourdough (dried crushed mother culture) of “Hors” TM and the powder of blue- green spirulina algae were used. The studied flour had a smell and taste peculiar to wheat flour, without any foreign odors and flavors. When chewing flour, there was no crunch. The wheat protein content (12.9 %) corresponded to the second grade of wheat used for food purposes. The gluten content of flour from Orzhitysia wheat grain corresponded to the gluten content of high grade flour and made 29.4 %, which is 4.4 % higher than the upper limit of the standard. Flour made from Orzhytsia wheat grain as to all quality indicators, corresponded to the accepted standards and the optimum level for obtaining high quality bread. Wild hop sourdough and hop sourdough of “Hors” TM changed such organoleptic characteristics of bread quality as bread volume and vesiculation. Adding hop starter cultures of “Hors” TM had a peculiar effect on the taste of bread – it had an unpleasant bitter taste. The using of spirulina and baking bread on hop sour- dough is a promising area. The results of the study enable us to recommend baking industry manufacturers the using of non-traditional mineral additives such as spirulina. It is expedient to use hop sourdough, espe- cially from wild hop, for baking non-yeasted (quick) wheat bread. Bread according to the new recipes, slightly differed from the control sample concerning its quality, the coloring in the samples where spirulina pulp was added had a greenish tinge, taste and smell peculiar to this herbal supplement. The bread baked on hop sourdough of wild hops had a brownish crumb, the taste and aroma pleasant but bitter.